AN EXPERIMENTAL DEMONSTRATION OF DIAMOND FORMATION IN THE DOLOMITE-CARBON AND DOLOMITE-FLUID-CARBON SYSTEMS - Sokol A.G.; Borzdov Y.M.; Pal'yanov Y.N.; Khokhryakov A.F.; Sobolev N.V. (My University, 2001)
The results of a study of diamond crystallisation in dry and fluid-rich dolomite-carbon systems are presented. For the dry system an induction period preceding spontaneous diamond nucleation was found of about 4 h at 7 GPa, 1700 degreesC. No diamonds were observed after 42 h of reaction at 5.7 GPa, 1420 degreesC. Adding H2O and H2O-CO2 fluids to the dolomite-carbon system resulted in spontaneous diamond nucleation at 1420 degreesC, and growth of diamond on seed crystals at 1300-1420 degreesC. In the presence of H2O or H2O-CO2 fluids, dolomite decomposes to dolomite solid solution + brucite + aragonite. Results of the experiments indicate that dolomitic melts in the mantle, enriched in H2O and CO2, promote the formation of natural diamond.
Keywords: diamond crystallisation; dolomite; carbon; fluid; HP/HT experiments